POLA PENYELENGGARAAN KEAKSARAAN DASAR SEBAGAI PROGRAM PENDIDIKAN NON FORMAL (Studi Kasus di SKB Bulukumba): (Studi Kasus di SKB Bulukumba) - Ilmar Andi Achmad; Muhammad Athar Asmas (Jurnal AKRAB, 2019)
A number of people in big cities today have tended to have different educational institutions were seen as more feasible and more appropriate for their children to attend school, educational institutions are called LCS. Bulukumba as one tourist city in Indonesia already has a community organizer for such an educational institution. Studio Learning Activities (SKB) which is located in Bulukumba shaft is one of the organizing institutions Basic Literacy (KD), which is well known and is a best practice to the institutions. Therefore these institutions should be reviewed and problems that need to be raised is how the home school operations carried out in the institution. This study aims to gain an overview of (1) the pattern of implementation SKB, especially with respect to curriculum, workforce, students, infrastructure, financing, institutional, and partnerships, and (2) the pattern of Education held in "SKB" Bulukumba, especially with respect to strategies implemented in the learning process they call with the term: comunity visit, home visit, and distance learning. To achieve the above objectives, the research was conducted with a qualitative approach with case study design. Information collected by (1) interview, (2) documentation, and (3) observation. Determination of resources starting from key informants and informant continued with another snowball. Data were analyzed with (1) data reduction, (2) the presentation of the data, and (3) a conclusion, and triangguluasi. The results of this study indicate that the pattern of implementation and learning patterns SKB Bulukumba very unique. The uniqueness can be seen from the curriculum applied a reference of learning for each student according to their learning needs. Characteristics of diverse learners shows that the educational services provided be multy multy grade and subject. The existence of the Internet is the primary requirement for continuity of the learning process. Competencies that must be mastered by the tutor as PP 19 In 2005 an absolute requirement that must be mastered by tutors who are responsible for assisting the process of learning. To improve the quality of service, network with other home school community is always woven by SKB Bulukumba. applied learning pattern by the Dolan School of three patterns, From these results, the suggestions put forward include (1) Have focused on the application of the concept of the approach leaders / stakeholders in the LCS, because the learning process is still focused on the learner. New parents just learning through asking and direct observation in the field. They have not yet fully used as a subject of study. Supposedly with the concept that the LCS is a home school, families of learners that should also be the subject of study, to be able to help learners outside of SKB, and (2) to support the orderly administration in organizing learning activities, where educators are indispensable.